Management of Islamic Boarding School Cooperatives Governance in Achieving Financial Sustainability: A Critical Synthesis of Dual Authority and Institutional Integration - Salman Alfarisi; Fauzan Fauzan; M.F Hidayatullah (LPPM STIES BABUSSALAM, 2026)
Islamic boarding school cooperatives (Koperasi Pesantren / Kopontren) hold strategic potential to drive the economic independence of the Muslim community in Indonesia. However, empirical evidence shows they frequently face low financial sustainability. This study systematically and critically reviews contemporary literature on the governance management of these cooperatives, focusing on integrating Good Corporate Governance (GCG) and Islamic Governance amidst complex cultural environments. Using a Systematic Literature Review (SLR) with a thematic synthesis approach, this study analyzes 22 journal articles and academic literature from Scopus, SINTA, and Google Scholar databases published between 2015 and 2024. The key findings reveal that financial sustainability failures are primarily triggered by the dualism of authority between the Kyai (charismatic authority) and professional managers (rational-legal authority). This dynamic leads to limited human resource capabilities, weak sharia compliance, and inadequate risk management. Furthermore, current literature remains largely descriptive and fails to provide empirical models measuring the direct impact of hybrid governance on financial ratios. This article contributes by proposing a new conceptual framework that bridges the cultural governance of pesantren with modern GCG standards, while defining specific research gaps for future empirical research on Islamic microfinance institutions